Virtual reality tourism and its impact to visitor intention in rural Bandung - Sobarna, Aditia; Saefullah, Kurniawan; Hadian, Sapari Dwi (Manajemen Komunikasi, 2024)
The use of virtual reality as a marketing tool for conventional tourism has seen an increasing adoption, as it enhances the engagement between virtual tourists and the showcased destinations. This study evaluates the effectiveness of Virtual Reality (VR) in enhancing the tourism experience at Alamendah Tourism Village, Bandung. A quantitative approach was used, with data collected through structured questionnaires distributed to 385 potential tourists who had experienced the village’s VR tour. Structural Equation Modeling (SEM) was employed to analyze the relationships between system quality, immersive perception, authenticity, satisfaction, and visit intention. The analysis process was supported by the SmartPLS application. The results indicate that system quality significantly influences immersive perception and authenticity, which in turn affects tourist satisfaction and visit intention. Moreover, immersive perception was found to mediate the relationship between system quality and authenticity. This study concludes that investment in high-quality VR technology and the creation of authentic immersive content is essential for tourism village managers to enhance tourist engagement and satisfaction. These findings suggest that VR can optimize the unique features of tourism villages, such as cultural authenticity and natural beauty. Additionally, VR can offer a deeper and more fulfilling experience when enjoying tourism in the village. Therefore, the implementation of VR can serve as a strategic tool to boost tourist loyalty and long-term success in the tourism village sector.